Evaluation of cellular network performance involving the LTE 1800 band and LTE 2100 band using the drive test method - Yuliarman Saragih; Ridwan Satrio Hadikusuma; Agatha Elisabet S (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
In the 4G Network on the cellular system, the possibility of high traffic increase is a big problem for users, the proposed solution is to reduce the possibility of full traffic and decrease the quality of the cellular system by dividing the frequency channel into several parts. The purpose of this paper is to study the effect of network optimization on the value of Key Performance Indicator (KPI) in the LTE 1800 and LTE 2100 bands. KPI values, In the LTE 1800 and LTE 2100 bands tested using the drive test method using the Telkomsel sim card provider, the results show that the LTE 2100 band on the TML 013 site has a very high CSSR number compared to the band LTE 1800 which is 99.73% after optimization. The results showed that the LTE band 2100 is better than the LTE band 1800 in terms of KPI Summary.